Development Of Elementary Schools Student-Athletes in Sragen Regency (Journal of Physical Education and Sports, 2021)
The research aimed to analyze and study developing elementary school student-athletes in Sragen Regency. Analyze and study the process of installing elementary school student-athletes in Sragen Regency. Analyze and study the nursery process of elementary school student-athletes in Sragen Regency. Analyze and study the process of guiding elementary school student-athletes in Sragen Regency. This research uses a descriptive qualitative approach. The subjects in this study were administrators, teachers, and students. This study uses data collection techniques with observation (observation), interviews (interview), documentation, and questionnaires. Data analysis techniques used data triangulation, namely data collection, data reduction, data presentation, and concluding. The results of this study are the coaching system that answers A (yes) = 63%, B (sometimes) = 32%, and C (no) = 4%. Regarding the coaching program, answer A (yes) = 58.21%, B (no) = 39.64%, and C (no) = 2.41%. Organizing answer A (yes) = 57.40%, B (sometimes) = 36.67%, and C (no) = 50%, B (sometimes) = 33.50%, and C (no) = 16.50%. The extracurricular that answered A (yes) = 60.83%, B (sometimes) = 30%, and C (no) = 9.17%. The training carried out in the elementary school in Sragen Regency went well. Recruitment of athletes as the next generation of achievements is slow and takes a long time. Training programs still tend to depend on field trainers and physical education teachers in their respective schools. Several extracurricular activities in school are not yet optimal. Facilities and infrastructure are sufficiently fulfilled. Sources of funds to finance coaching programs in schools through extracurricular programs can be obtained from the assistance of the committee, parents, and teachers themselves.